KOMODIFIKASI AGAMA DALAM SISTEM KAPITALISME UNTUK MENUNJANG MINAT KONSUMEN - Yosinta Paramba’; Mirna; Stevani Mentang Salu Panggalo; Crepelin Mawarni (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
In the capitalist system, capitalists view religion not only as a belief system, but religion is also seen as something that can be used as a tool for commercialization, even though religion is basically not something that can be commercialized. In this case, religion is commodified into the capitalist system to support marketing and gain large profits. Values, teachings, symbols, and religious figures are commodified into the market system as tools for exploitation in order to obtain maximum profit. The method used in this writing is a literature study by collecting various information related to the commodification of religion in the capitalist system through books, journals, articles, and so on.